Polyethylene microplastics promote nucleus pulposus cell senescence by inducing oxidative stress via TLR4/NOX2 axis - Weilin Zhang; Zhencong Li; Zhongwei Wang; Kuize Liu; Shengbang Huang; Jinguo Liang; Zhiwen Dai; Weixiong Guo; Chao Mao; Siyuan Chen; Jinsong Wei (Ecotoxicology and Environmental Safety)
This study aimed to detect and characterize microplastics in intervertebral disc and investigate their effects and molecular mechanism on intervertebral disc degeneration. We collected intervertebral disc tissues from cervical, lumbar, and thoracolumbar segments and used Raman spectroscopy to identify and characterize microplastics. Among 80 samples, 47 contained microplastics, with polyethylene being the most prevalent type. To explore the effects of polyethylene microplastics (PE-MPs), we established a mouse model and a nucleus pulposus cell model. Reactive oxygen species (ROS) levels were assessed via immunofluorescence staining, cell viability was measured using the CCK-8 assay, and protein expression related to the Toll-like receptor 4 (TLR4)/NADPH oxidase 2 (NOX2) axis, oxidative stress, and nucleus pulposus degeneration were evaluated through western blotting and immunofluorescence staining. Results showed that PE-MPs exposure led to intervertebral disc degeneration by inducing oxidative stress and activating the TLR4 / NOX2 axis, which increased the senescence of nucleus pulposus cells. These effects were mitigated by TLR4 and NOX2 inhibitors. This research highlights the existence of microplastics in human intervertebral disc tissue and unveils a novel mechanism of nucleus pulposus cell senescence induced by PE-MPs, offering new avenues for clinical treatment of microplastic-related disc degeneration.